2018
DOI: 10.4103/aam.aam_36_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of high resolution ultrasound complementary to digital mammography

Abstract: Background:Breast carcinoma is a major cause of mortality among women worldwide. Early detection and cure is the key to reduce the mortality of the disease. This article studied the role of high resolution ultrasound in detection and characterization of lesions to complement mammographic diagnosis and improve patient management.Aims and Objectives:To evaluate the role of complementary high resolution ultrasound, BIRADS scoring and to correlate it with histological diagnosis.Results and Observations:HRUS is exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…4 USG, MRI and molecular breast imaging are usually not considered as primary screening tools and are employed as adjuncts to assess the abnormalities detected in MMG. 5 American college of radiography developed the breast-imaging reporting and data system (BI-RADS) lexicon, a standard terminology used to summarize the findings of various breast-imaging techniques such as MMG, USG and MRI. 4 We too employed the BI-RADS lexicon in our study.…”
Section: Introductionmentioning
confidence: 99%
“…4 USG, MRI and molecular breast imaging are usually not considered as primary screening tools and are employed as adjuncts to assess the abnormalities detected in MMG. 5 American college of radiography developed the breast-imaging reporting and data system (BI-RADS) lexicon, a standard terminology used to summarize the findings of various breast-imaging techniques such as MMG, USG and MRI. 4 We too employed the BI-RADS lexicon in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the spatial resolution of liver ultrasound images can affect one's ability to discriminate hemangiomas, and the proposed algorithm is expected to provide significant advantages in this regard. Improving the spatial resolution of breast ultrasound imaging is an effective method for detecting fine calcific formations, and it has been reported that a sensitivity of up to 95% is achievable [45]. In addition, breast ultrasound images with improved spatial resolution can be used better distinguish between solid and cystic lesions and characterize their complexity [46].…”
Section: Resultsmentioning
confidence: 99%
“…Breast ultrasound is a non-invasive, relatively available imaging modality that is used as complementary to mammography in screening especially in dense breasts, differentiation of solid and cystic lesions, characterization of lesions, and diagnosis of intraductal mass as well as problem-solving for mammographically detected asymmetries [12,13].…”
Section: Discussionmentioning
confidence: 99%